PENTINGNYA TEKNIK LOBI DAN NEGOSIASI DALAM KOMUNIKASI BISNIS - Rita Dwi Lestari Hulu; Muhammad Fahmi Habib, Resa Shin Tia, Fitri Maulida Husna, Suhairi (CV. ADIBA AISHA AMIRA, 2023)
Lobbying and negotiation are 2 things that cannot be separated from our daily lives, whether we are aware of it or not, because in solving a problem or differences of opinion and interests, deliberation is needed through lobbying and negotiation, although sometimes this is done for a relatively long time. Lobbying as an approach in the context of negotiating. Lobbying and negotiation can run successfully if it is done well and in the lobbying and negotiation process it always involves a communication process in it both verbal and nonverbal communication, this is what causes lobbying and negotiation techniques to be important in business communication, because in business communication, negotiation is a process in which two parties or more have the same interests, meet and hold joint meetings to reach an agreement that is securely acceptable to all parties without burdening any party. In lobbying and negotiating, we must use strategies, techniques and tactics. This study aims to analyze